2022
DOI: 10.1123/ijspp.2021-0345
|View full text |Cite
|
Sign up to set email alerts
|

There Is No Global Running Pattern More Economic Than Another at Endurance Running Speeds

Abstract: Purpose: The subjective Volodalen® score (V®score) and the objective duty factor metric can both assess global running patterns. The authors aimed to investigate the relation between running economy (RE) at endurance running speeds and the global running pattern quantified using both subjective and objective measures. Methods: RE and 3-dimensional whole-body kinematics were acquired by indirect calorimetry and an optoelectronic system, respectively, for 52 trained runners during treadmill runs at 10, 12, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Indeed, several studies report similar oxygen uptake (for a normalised mass) and net metabolic rate between RFS and FFS runners at different sub-maximal speeds. [23][24][25] Again, Anderson et al 21 do not recommend, following their systematic review with meta-analysis, to modify the footstrike pattern of their endurance runners to improve their running economy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies report similar oxygen uptake (for a normalised mass) and net metabolic rate between RFS and FFS runners at different sub-maximal speeds. [23][24][25] Again, Anderson et al 21 do not recommend, following their systematic review with meta-analysis, to modify the footstrike pattern of their endurance runners to improve their running economy.…”
Section: Introductionmentioning
confidence: 99%
“…Running shoes act as an interface between the foot and the ground and play a central role in running. Running shoes are constantly evolving [1,2], as is the research on running biomechanics and footwear [3][4][5]. Experts agree that comfort, injury prevention, and performance are important factors to consider in the design and manufacturing of running footwear [6]; however, these topics are often complex to investigate due to their multifactorial [7][8][9], individualised [10,11], or subjective [7] nature with no clear evidence-based direction for footwear prescription [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…RE (in mLO 2 ∙kg −1 ∙km −1 ) was 215.7 ± 13.6, 220.4 ± 11.1, 216.3 ± 10.0 for the midfoot group at speeds 3.06 m∙s −1 , 3.61 m∙s −1 and 4.17 m∙s −1 , respectively Stationary gas analyzer (Ergocard; Medisoft Group, Sorinnes, Belgium); 3.06, 3.61, 4.17 m∙s −1 ; 6 min; last 3 min used for data analysis; RER < 1.0 b mLO 2 ∙kg −1 ∙min −1 and mLO 2 ∙kg −1 ∙km −1 ; n.a. ; no subtraction reported Concurrent; contact laser platform; treadmill; shoes not standardized; right side Step length; step frequency; foot strike pattern; contact time; step length; flight time Pastor et al [ 118 ]; correlational 17/0; road runners ( n = 7) 27 ± 4.8; 177.1 ± 6.7; 62.6 ± 3.9; not reported Trail runners ( n = 10) 30.8 ± 8.3; 176.7 ± 6.7; 65.6 ± 5.6; not reported Members of national team; road PB 10 km 29:17 average with times ranging from 28:06 to 30:56 for road runners, trial runners performance index of 864 points; no weekly training distance, running experience, or reported; RE (in J∙kg −1 ∙m −1 ) was 4.37 ± 0.27 for trail runners and 4.09 ± 0.31 for road runners at 2.78 m∙s −1 , and RE was 4.32 ± 0.22 for trail runners and 4.06 ± 0.29 for road runners at 3.89 m∙s −1 Portable gas analyzer (Metamax 3B, Cortex, Leipzig, Germany); 2.78 and 3.89 m∙s −1 ; 4 min; last min used for data analysis; increase in < 100 mLO 2 ∙min −1 and RER < 1.0 b J∙kg −1 ∙m −1 ; Péronnet equation; no subtraction reported Concurrent; optoelectronic system; treadmill; not reported; not reported Flight time; contact time; step frequency; duty factor; leg stiffness; vertical stiffness Patoz et al [ 99 ]; correlational 31/21; males: 31 ± 8; 174 ± 7; 66 ± 10; not reported Females: 32 ± 9; 162 ± 4; 52 ± 5; not reported Trained runners; recent half-marathon times: males 91 ± 9 min, females: 102 ± 9 min; weekly training distance: males 55 ± 19 km, females 50 ± 21 km; Experience: males 8 ± 6 years, females 7 ± 4 years; and RE not reported Stationary gas analyzer (TrueOne 2400, Parvo Medics Inc., Sandy, UT, USA); 2.78, 3.33, and 3.89 m∙s −1 ; 4 min; last min used for data analysis; visual inspection of and and RER < 1.0 …”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported RE in multiple units, and thus the total is higher than 51. Forty studies described methods used to check for a steady state, which included verification of the respiratory exchange ratio below 1.0 (22 studies [ 24 , 39 , 40 , 80 , 81 , 86 , 88 90 , 93 104 ], measurement of blood lactate concentration (12 studies [ 23 , 24 , 40 43 , 82 , 92 , 105 – 108 ]), and visual inspection of a plateau in the oxygen consumption ( ) and/or carbon dioxide expired data (21 studies [ 34 , 35 , 39 , 80 , 82 , 84 86 , 88 90 , 94 96 , 98 , 99 , 106 , 109 112 ]). Most studies ( k = 18) employed multiple methods to check for steady state [ 32 , 83 , 87 , 113 120 ], while 11 studies did not report any steady-state verification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation